GERAKAN AKTIFKAN POSYANDU : UPAYA PENINGKATAN KAPASITAS KADER DALAM AKSELERASI CAPAIAN POSYANDU DI DESA GOMBONGSARI, KABUPATEN KARAWANG - Desy Rizki Ariani; Uun Nurjanah; Abdul Gowi; Siti Sopiatun; Lilis Siti Khodijah; Kustiyuwati Kustiyuwati; Sri Ayu Fatmayanti (Jurnal Abdimas Indonesia, 2025)
Posyandu is one form of community empowerment aimed at improving public health, particularly for mothers and children. It serves as one of the spearheads of public health services in Karawang. However, challenges still exist in Posyandu services, including the level of participation of toddlers and the capacity of cadres in carrying out Posyandu activities. Gombongsari Village is a village where most of the residents are farmers. This village has been designated as a model village in Karawang Regency to compete in the National-level P2WKWS program.P2WKWS is an integrated assessment activity aimed at evaluating the success of villages or urban wards in empowering women’s roles in family development, particularly in health aspects, in this case, Posyandu. In response to this, a strategic step was needed to reactivate the “Activate Posyandu” movement as an effort to increase the capacity of Posyandu cadres to accelerate the achievements of Gombongsari Village Posyandu.The cadres were provided with training and education on Exclusive Breastfeeding (ASI Eksklusif), complementary feeding (MP-ASI) and animal protein-rich foods, as well as nutritional status and its management. The results of this community service activity showed a significant increase before and after the intervention in education on Exclusive Breastfeeding, complementary feeding and animal protein-rich foods, as well as nutritional status and its management (p-value = 0.001, p-value = 0.001, p-value = 0.001).The success of this intervention was supported by the delivery of materials relevant to the cadres’ field conditions, engaging media, and effective delivery methods. This proves that providing interventions effectively improves cadres’ knowledge capacity. With the increased understanding and capacity of the cadres, it is expected that they will be able to improve health services at the Posyandu.